A vertical graphene enhanced Zn–MnO2 flexible battery towards wearable electronic devices. Issue 1 (17th December 2020) - Chen, Junyan; Liang, Jiaxing; Zhou, Yang; Sha, Zhao; Lim, Sean; Huang, Feng; Han, Zhaojun; Brown, Sonya A.; Cao, Liuyue; Wang, Da-Wei; Wang, Chun H.
Abstract : A multilayer structured cathode for zinc ion batteries is created by using vertical graphene nano-maze to hold MnO2 and encapsulating with an ionic conductive PEDOT:PSS layer. The new electrode exhibits exceptional capacity and cycle performance. Abstract : The growing interest in wearable electronics has stimulated recent advances in flexible Zn–MnO2 batteries. However, the electrochemical performance of bulk MnO2 is limited by its poor electrical conductivity and inferior charge kinetics. Herein, we propose a novel MnO2 -vertical graphene cathode to markedly improve the electrochemical performance of Zn batteries. By embedding a MnO2 nanomaterial in a highly conductive network of vertical graphene (VG) nanosheets, a new electrode is created for zinc ion batteries, with the 3D nano-maze microstructure of the graphene nanosheets providing conductive tunnels for fast electron and charge transfer. The condensed carbon buffer layer that connects the VG nanosheets with the carbon fiber substrate boosts the reaction kinetics further. With the final protective layer incorporating a poly(3, 4-ethylenedioxythiophene)–poly(styrenesulfonate) (PEDOT:PSS) conductive network encapsulating the electrode, the VG-MnO2 -PEDOT:PSS nanostructured composite electrode delivers an unprecedented capacity of 367.4 mA h g −1 based on the mass of the active material, as well as maintains a tremendous 73.7% retention of charge after 1000 cycles in an aqueous electrolyte. Furthermore, the as-assembled quasi-solid-state Zn–MnO2 battery demonstrates excellent electrochemical stability under several mechanical loading conditions and achieves a high energy density of 400.2 W h kg −1 at a power density of 0.68 kW kg −1 . Overall, the demonstrated method in this study has great potential to provide high performance flexible Zn–MnO2 batteries for powering future wearable electronic devices.